Merawat Kerukunan Hidup Umat Beragama dalam Pandangan Hindu - Juniartha, Made G; Arimbawa, I Komang Suastika (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2020)
Today's religious life has entered a period of crisis, where 'loyalty' to religion has begun to lead to an exclusive ideology that can threaten diversity. In addition, religion also began to be used as a 'political weapon' to attack its opponents. This is a big challenge for religious people in social life. The role of religious leaders is highly expected in the effort to restore religion to its 'spirit', as a 'shade' of humanity so that harmony can be realized. The harmony of life is one of the realization of religious teachings to achieve the highest goal of life, namely eternal peace, which in Hindu teachings is called Moksa. There are various concepts offered in an effort to care for harmony in the Hindu view, such as the concept of universal brotherhood (Lokasamgraha), Vasudaiva Kutumbhakam, Tat Tvam Asi, and Tri Hita Karana. In addition, efforts can be made in caring for harmony in life, namely by reducing religious radicalism notions with humanismreligious values. The hope, with the 'enlightenment', religious people can understand the nature of diversity in a plural environment, so that harmony of life will undoubtedly be realized.